Current Approaches to Valerian Tincture Standardisation in Terms of Assay - N. P. Antonova; E. P. Shefer; A. M. Kalinin; N. E. Semenova; S. S. Prokhvatilova; I. M. Morgunov (Регуляторные исследования и экспертиза лекарственных средств, 2019)
The quality control of the «Valerian rhizome and roots» herbal substance is carried out using high performance liquid chromatography (HPLC) according to the State Pharmacopoeia of the Russian Federation, XIV edition. The quantitative analysis of the active ingredients in valerian tincture is performed using a non-specific and non-selective spectrophotometric method. Therefore, it is important to introduce in Russia a more modern test procedure for quantitative determination of active ingredients in valerian tincture.The aim of the study was to develop a selective and sensitive HPLC procedure for quantitative determination of the total content of sesquiterpenic acids, expressed as valerenic acid, for the purpose of valerian tincture standardisation.Materials and methods: valerian tincture samples produced by seven Russian manufacturers were used as test samples, and valerenic acid was used as the reference standard. The quantitative analysis of the active ingredients was performed by two methods: spectrophotometry at 512 nm following the reaction of valerenic acid ethylester with hydroxyalamine and ferric chloride, and by HPLC using a Nucleosil C18 column, 125×4.6 mm, 5 µm particle size, in gradient elution mode, with detection at 220 nm.Results: the spectrophotometric technique was shown to be insufficiently specific. The authors of the study validated the chromatographic test procedure, established system suitability criteria, and compared the results obtained by the two test procedures. They also determined a tentative standard of the total content of sesquiterpenic acids, expressed as valerenic acid, obtained by HPLC.Conclusions: the HPLC assay developed for quantitative determination of active ingredients in valerian tincture is more specific as compared to the spectrophotometric technique, as the sum of the peaks of valerenic and acetoxyvalerenic acids and the results for the reference standard are taken into account during calculations. The new test procedure is in line with the cross-cutting standardisation principle and can be recommended for inclusion into the draft monograph «Valerian tincture».